Errors and Complications in SQL Query Formulation - Taipalus, Toni; Siponen, Mikko; Vartiainen, Tero (Association for Computing Machinery, 2018)
SQL is taught in almost all university level database courses, yet SQL has received relatively little attention in educational research. In this study, we present a database management system independent categorization of SQL query errors that students make in an introductory database course. We base the categorization on previous literature, present a class of logical errors that has not been studied in detail, and review and complement these findings by analyzing over 33,000 SQL queries submitted by students. Our analysis verifies error findings presented in previous literature and reveals new types of errors, namely logical errors recurring in similar manners among different students. We present a listing of fundamental SQL query concepts we have identified and based our exercises on, a categorization of different errors and complications, and an operational model for designing SQL exercises.
Keywords: errors; exercise design; human factors; query languages; standardization; SQL; fi=Tietotekniikka|en=Computer Science|